Determinants of Delayed Inpatient Claims in an Indonesian Hospital: Faktor-faktor yang Mempengaruhi Penundaan Klaim Pasien Rawat Inap di Rumah Sakit di Indonesia - Apvinia May Savitri; Resta Dwi Yuliani (Academia Open, 2025)
General Background: Hospital reimbursement under national health insurance systems relies on complete medical records, accurate clinical coding, and timely administrative processing to ensure continuity of health service financing. Specific Background: Preliminary findings at Siti Fatimah Tulangan Hospital Sidoarjo revealed pending inpatient claims caused by inaccurate diagnosis coding, discrepancies between clinical documentation and medical resumes, and coder workload issues. Knowledge Gap: Limited qualitative evidence exists regarding how behavioral, organizational, and procedural factors jointly contribute to claim delays in hospital settings using the INA-CBG payment system. Aims: This study sought to identify determinants of delayed inpatient claims using the Multiple Criteria Utility Assessment method within a descriptive qualitative framework. Results: Data from interviews and observations involving a coder, a medical record officer, and a nurse indicated that delays were associated with predisposing factors (coder attitude, education background, limited training, and coordination barriers with physicians), enabling factors , and reinforcing factors  Novelty: The study integrates behavioral health theory components—predisposing, enabling, and reinforcing factors—with MCUA prioritization to analyze administrative claim delays in a hospital context. Implications: Addressing communication gaps, strengthening procedural dissemination, and improving organizational support mechanisms are necessary to reduce pending claims and maintain hospital financial stability. Highlights: Incomplete clinical documentation after patient discharge frequently prolonged reimbursement processing. Independent troubleshooting by coding staff occurred without sufficient coordination with responsible physicians. Organizational support and procedural dissemination were insufficient despite existing formal guidelines. Keywords: Inpatient Claims; Medical Coding; INA-CBG; Hospital Administration; Qualitative Study